Legal rules to combat terrorism in Iraq - Ibrahim, Zeyad Tareq (International Journal of Scientific Research and Management (IJSRM), 2019)
The phenomenon of terrorism is the most important challenge facing successive Iraqi governments after the events of 2003, the impact of the problem has increased due focus of the media in various aspects of the problem  as it has become a threat to all humanity, the Intellectual extremism and religious extremism are among the most important sources of violence and terrorism, so the intellectual terrorism is being exploited by militant groups which committed the worst crimes by its name and turned from small groups into militias possessing heavy and sophisticated weapons.The Iraqi legislations related to the phenomenon of terrorism shows that Iraq has followed most of the national legislation of the countries around the world. So the Iraqi Constitution contained provisions prohibiting terrorism. and the Iraqi legislator also adopts the pro-Iraqi trend  to issue a special and independent law, where the National Assembly issued the anti-terrorism law No. 13-2005). and followed by the legislator in Kurdistan of Iraq, where he issued a law against terrorism No.3- 2006.